Familial, autosomal-dominant neurodegenerative parkinsonism with cognitive deterioration spanning five generations in a genetically isolated population of south-eastern Moravia, Czech Republic - Mensikova, Katerina; Godava, Marek; Kanovsky, Petr; Otruba, Pavel; Kaiserova, Michaela; Vastik, Miroslav; Mikulicova, Lenka; Bartonikova, Tereza; Vrtel, Radek; Vodicka, Radek; Kurcova, Sandra; Jugas, Petr; et al. (Biomedical papers, 2016)
Background: An epidemiological study conducted over four years revealed increased prevalence of neurodegenerative parkinsonism in a small, isolated region (10 villages, with a combined population of 8664, with approx. 2927 over 50 years of age) of south-eastern Moravia, Czech Republic. The aim of this study was to obtain more detailed information on the medical history of the relatives of individuals with confirmed parkinsonism in an isolated rural population in south-eastern Moravia, Czech Republic.Methods: We did detailed genealogical research on the families of all inhabitants with confirmed parkinsonism and compiled the pedigrees. These were modified on the basis of information from a consecutive door-to-door survey and local municipal and church registers.Results: In the first stage, three large pedigrees with a familial occurrence of parkinsonism were found; two originated in one of the region's villages. In the second stage, these two pedigrees were combined into one large family tree.Conclusions: The high prevalence of parkinsonism in the researched area is caused by the familial aggregation of parkinsonism that was found in two large family trees. This is probably the result of the genetic isolation of the regional population due to the very low migration rate of its inhabitants to neighboring regions in the last two centuries.
Keywords: parkinsonism; cognitive deterioration; isolated population; neuroepidemiology; genealogy